An epidemiological study on anemia among institutionalized people with intellectual and/or motor disability with special reference to its frequency, severity and predictors - Tomono Yuji; Nara Nobuo; Nakayama Takeo; Ohwada Hiroko; Yamanaka Keiko (BMC, 2006)
Abstract Background To examine the type, frequency, severity, and predictors of anemia and its relationship with co-morbid conditions among institutionalized people with intellectual and/or motor disability. Methods We conducted a cross-sectional study at a public facility for people with intellectual and/or motor disability in Ibaraki prefecture, Japan. Health checkup data obtained in 2001 from 477 people with intellectual disability (male: 286, average age 40.6 ± 12.3; female: 191, average age 45.1 ± 11.6) were retrospectively reviewed. Results The prevalence of anemia among male participants was higher than in female participants for each disability category (intellectual disability, 41.1%, 4.2%; cerebral palsy, 37.5%, 4.8%; Down's syndrome, 15.0%, 0%; severe motor and intellectual disabilities, 61.9%, 16.7%). Most participants with anemia (93.8 - 100%) showed a normocytic normochromic anemia pattern. Multivariate analysis revealed that factors related to an increase in frequency included sex (male), low body mass index (BMI), use of anticonvulsants or major tranquilizers, and a high zinc sulfate turbidity test (ZTT) value. No clinically diagnosed co-morbid condition was found to be related to the presence of anemia. Conclusion A high frequency of mild normocytic normochromic anemia in institutionalized people with intellectual and/or motor disability was observed, particularly among males. Medications and chronic inflammation may increase the risk of anemia.